Comparative study of Tris Turmeric, Tris Turmeric Dimethyl Sulfoxide and Tris Turmeric Ethylene glycol extenders on the cryosurvivability, sperm resistance, in- vivo fertility and antioxidant status in buffalo bull semen - El-Sheshtawy, Reda Ibrahim; Said Kotp, Mohamed; Abd El-Aziz, Tamer Helmi (Buffalo Bulletin, 2024)
The freeze-thaw process leads to structural and functional damage due to excessive accumulation of reactive oxygen species (ROS). The addition of exogenous antioxidants to sperm diluents is of great importance to overcome oxidative damage during freezing. The purpose of this study was to explore the effects of three diluents Tris Turmeric, Tris Turmeric Dimethyl Sulfoxide and Tris Turmeric Ethylene glycol on the cold survival ability of buffalo sperm. Semen was collected from five local adult male buffalo breeds. A base diluent of Tris-citric acid-fructose (TCF) was prepared, adding 20% whole egg yolk (TCFY). The Tris extender without turmeric, without DMSO, and without EG was kept as a control. Other extenders are Tris containing turmeric TT (100 ml/5 ml Tris), Tris containing turmeric dimethyl sulfoxide TTD (100 ml/5 ml Tris + 1.5% DMSO) and Tris containing turmeric and ethylene glycol TTE EG (100 ml/5 ml Tris + 1.5% EG). Semen samples were added and a pure sperm concentration of 60 × 106/ml was achieved. Frozen buffalo sperm after thawing showed significant improvements in all research parameters of the three breeding samples compared to the control. Tris Turmeric Ethylene was the type that best improved sperm survival under frozen conditions, followed by Tris Turmeric and Tris Turmeric Dimethyl Sulfoxide compared to the control. A significant decrease in sperm motility after thawing was evident as usage time increased in all expanders. There was a significant increase in total antioxidant content (TAC) and insignificant change in malondialdehyde (MDA) of the diluent used compared to the control. Conception rate (CR) was higher in Tris Turmeric Ethylene glycol (65.2%), followed by Tris Turmeric (60.3%) and Tris Turmeric Dimethyl Sulfoxide (55.9%) compared to the control (36, 7%). It can be concluded that Tris Turmeric Ethylene Glycol is considered the best agent for improving cold survival and sperm fertility, followed by Tris Turmeric and Tris Turmeric Dimethyl Sulfoxide.